GSK1265744 pharmacokinetics in plasma and tissue after single-dose long-acting injectable administration in healthy subjects - Spreen, William; Ford, Susan L; Chen, Shuguang; Wilfret, David; Margolis, David; Gould, Elizabeth; Piscitelli, Stephen (Journal of acquired immune deficiency syndromes (1999), 2014)
GSK1265744 (744) is an HIV-1 integrase inhibitor in clinical development as a long-acting (LA) injectable formulation. This study evaluated plasma and tissue pharmacokinetics after single-dose administration of 744 LA administered by intramuscular (IM) or subcutaneous injections. This was a phase I, open-label, 9-cohort, parallel study of 744 in healthy subjects. 744 was administered as a 200 mg/mL nanosuspension at doses of 100-800 mg IM and 100-400 mg subcutaneous. Eight (6 active and 2 placebo) male and female subjects participated in each of the first 7 cohorts. All 8 subjects, 4 males and 4 females, received active 744 LA in cohorts 8 and 9 and underwent rectal and cervicovaginal tissue sampling, respectively. Plasma pharmacokinetic sampling was performed for a minimum of 12 weeks or until 744 concentrations were ≤0.1 μg/mL. Rectal and cervicovaginal tissue biopsies were performed at weeks 2 and 8 (cohort 8) and weeks 4 and 12 (cohort 9). 744 LA was generally safe and well tolerated after single injections. A majority of subjects reported injection site reactions, all graded as mild in intensity. Plasma concentration-time profiles were prolonged with measureable concentrations up to 52 weeks after dosing. 744 LA 800 mg IM achieved mean concentrations above protein adjusted-IC90 for approximately 16 weeks. Rectal and cervicovaginal tissue concentrations ranged from <8% to 28% of corresponding plasma concentrations. These data suggest 744 LA injection has potential application as a monthly or less frequent HIV treatment or prevention agent.